2022
DOI: 10.3389/falgy.2022.824717
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic Properties and Molecular Characteristics of PR-1 Proteins

Abstract: Only a small fraction of proteins in plants and animals are classified as allergens. The allergenic properties are frequently attributed to certain functional characteristics of the proteins, such as a role in the plant defense against biotic and abiotic stress, to achieve the systematic acquired resistance. In line with this, eight members out of 17 functional pathogenesis-related (PR) protein families have been characterized as allergens. The present review summarizes the molecular features and allergenic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…They are among the most strongly expressed and abundant PR proteins and can account for up to 2% of total leaf proteins in tobacco (Lu et al, 2011 ; Niderman et al, 1995 ; van Loon & van Kammen, 1970 ; van Loon & van Strien, 1999 ). Some PR1 family members from tomato, potato, oilseed rape, and maize have IgE‐sensitizing capacity and thus act as plant allergens (Wangorsch et al, 2022 ). Most PR1 family members contain only a CAP domain and relatively short C‐ and N‐terminal extensions, indicating that the CAP domain determines their function in plant pathogen defence.…”
Section: Plants Recognize Pathogens and Mount An Immune Responsementioning
confidence: 99%
“…They are among the most strongly expressed and abundant PR proteins and can account for up to 2% of total leaf proteins in tobacco (Lu et al, 2011 ; Niderman et al, 1995 ; van Loon & van Kammen, 1970 ; van Loon & van Strien, 1999 ). Some PR1 family members from tomato, potato, oilseed rape, and maize have IgE‐sensitizing capacity and thus act as plant allergens (Wangorsch et al, 2022 ). Most PR1 family members contain only a CAP domain and relatively short C‐ and N‐terminal extensions, indicating that the CAP domain determines their function in plant pathogen defence.…”
Section: Plants Recognize Pathogens and Mount An Immune Responsementioning
confidence: 99%
“…Among the 31 selected effector candidates, an interesting finding is that effector candidate Mycgr3109710 localizes to the nucleus and labels mobile cytosolic bodies that are predominantly located at the cell periphery when expressed in Nicotiana . This effector candidate is annotated as a member of the Allergen V5/Tpx-1 related group, which are cysteine-rich secretory proteins (Crips) including proteins of the PR-1 family and potent allergens (Wangorsch et al, 2022). Protein feature analysis using InterProScan revealed cystine-rich secretory proteins, antigen 5, and pathogenesis-related 1 proteins (CAP) and sperm-coating protein (SCP) domains in Mycgr3109710, indicating its association with the homologous PR-1-like superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…An in-depth characterisation of the wasp venom proteome and transcriptome revealed that it is rich in various types of hyperallergic components, including arginine kinase, CAP, hyaluronidase, maltase, and phospholipase ( Figure 2 ; Supplentary Table S3 ), which have been previously reported from several hymenopterans ( Bilo et al, 2005 ; Hoffman et al, 2005 ; Hemmer and Wantke, 2020 ). The CAP superfamily of proteins that constituted nearly one-fourth of the wasp venom proteome (∼26%), are well-known for their role in inhibiting various ion-channels, modulation of vascular permeability and eliciting IgE-mediated immune reactions ( Tadokoro et al, 2020 ; Wangorsch et al, 2022 ). Similarly, hymenopteran PLA 1 s, which constitute 21.86% of the V. affinis venom, are shown to be hyperallergic ( Sookrung et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%